Susceptibility to Phytophthora cinnamomi of the commonest morphotypes of Holm oak in southern Spain (Forest Pathology, 2012)
The four main morphotypes of Holm oak (Quercus ilex subsp. ballota) present in Andalusia (expansa, macrocarpa, microcarpa and rotundifolia) were infected with Phytophthora cinnamomi to determine their susceptibility to the root pathogen. No large differences were found among the four morphotypes in the infection of roots, which always showed a high degree of necrosis. However, the different responses of the foliage to infection separated the four morphotypes of Holm oak into three groups: very susceptible (microcarpa), susceptible (expansa) and moderately susceptible (rotundifolia and macrocarpa). The natural hybrid Q. ilex ballota–Q. faginea exhibited a low level of root and foliar symptoms when infected with P. cinnamomi. Quercus faginea could be considered as a source of resistance to P. cinnamomi in future breeding programmes.